Perancangan system informasi sekolah berbasis website di SMP IT Al Irsyad Al Islamiyyah Indramayu (Current Research in Education: Conference Series Journal, 2023)
School the facilities in the field of education that can provide the best services or facilities for students and also for parents, supporting services, namely school information. The process of disseminating information at SMP IT Al Irsyad Al Islamiyyah is still done manually by distributing brochures. Therefore, there are often delays or errors in processing, including not being up to date with existing data or disseminating information that is deemed less effective and efficient. The purpose of this study was to produce a website-based school information system design at SMP IT Al Irsyad Al Islamiyah Indramayu with an information dissemination system such as a website for school progress and development. The research method used is the Research and Development (RD) research method. The results of this study can implement the results of the school information system design in order to make it easier to get school information quickly and accurately. By utilizing the correct and good school website, the pattern of information dissemination will continue to be up to date.